Ibuprofen-induced pityriasis rosea and fixed-drug eruption - Debasmita Behera; Chinmoy Raj; Sejal Bajoria; Kriti Jain; Riya Sukhija (Wolters Kluwer Medknow Publications, 2024)
Pityriasis rosea (PR) is a common acute and usually self-limiting papulosquamous dermatosis that typically affects children and young adults. Fixed-drug eruption (FDE) is a type of cutaneous adverse drug reaction that reoccurs at the same site when the offending drug is reingested. We are presenting this case of a 2-year-old child because of the simultaneous presentation of both PR and FDE in the same individual at the same time.